An optimal control method for small-scale GSHP-integrated air-conditioning system to improve indoor thermal environment control. (1st November 2022) - Gao, Jiajia; Yan, Junjun; Xu, Xinhua; Yan, Tian; Huang, Gongsheng
Abstract: ON/OFF controlled ground-source heat pump (GSHP) is often integrated with small-scale central air-conditioning system (ACS) for villas. Chilled-water temperature (CHWT) in this system usually oscillates in a large range due to the ON/OFF switch of the compressor. As it may be too high or too low, the cooling output of the air-handling unit (AHU) in its adjustable range may not be coincident with the indoor cooling demand, which may lead to unsatisfactory room temperature control performance. This study proposes an optimal control method for this system to improve the control robustness of the room temperature. Usually, the variation of indoor cooling-load is transferred to the chilled-water resulting in changing water temperature. In this method, the optimal chilled-water return (CHWR) temperature is calculated on the basis of the estimated sensible heat load and total cooling-load of the concerned rooms. Then, this CHWR temperature is reset following up the ON and OFF states of the compressor to regulate the variation range of the CHWT. Thus, the cooling output of the AHU in its adjustable range can always follow up the changing of indoor cooling demand. This method is tested on a simulation platform and a real ACS. The test results show good temperature control performance can be achieved. The experimental results demonstrate that the maximum deviation of room temperature is reduced by 2°C and the energy consumption of the GSHP and fan can be reduced by 30.12% at light cooling-load. The application performance shows this method can be easily realized in a common building automation system. Highlights: An optimal control method is developed for an on/off controlled GSHP-integrated ACS. The CHWR temperature is optimized and reset based on the estimated indoor cooling load. The cooling output of AHU is regulated to always satisfy the changing of the indoor cooling demand. This control method is tested on a simulation platform and a real air conditioning system. The good temperature control performance and energy performance are achieved.